2011
DOI: 10.1002/bjs.7342
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of procedure-based assessment for assessing trainees' skills in the operating theatre

Abstract: PBA demonstrated good overall validity and acceptability, and exceptionally high reliability. Trainees should be assessed adequately for each given procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 10 publications
(11 reference statements)
2
97
0
6
Order By: Relevance
“…36 Procedure-based assessment includes "exposure" and "technique." 37 And the Ottawa Surgical Competency Operating Room Score uses "knowledge of procedural steps." 38 But none of these rubrics fully capture the pattern of principles represented in this study.…”
Section: Acknowledging Challenges In Assessmentmentioning
confidence: 99%
“…36 Procedure-based assessment includes "exposure" and "technique." 37 And the Ottawa Surgical Competency Operating Room Score uses "knowledge of procedural steps." 38 But none of these rubrics fully capture the pattern of principles represented in this study.…”
Section: Acknowledging Challenges In Assessmentmentioning
confidence: 99%
“…Nonetheless, regardless of the method or technology used, if the simulation provides appropriate fidelity (faithfulness of reproduction) for key components of the task, it is likely that consistent and uniform skills may be learned and assessed using computer-based methods. This contrasts with the unpredictability and bias of patient-based training and assessment [17].…”
Section: What Can We Expect From the Technology?mentioning
confidence: 66%
“…17 PBA assessments are now a well-established, validated method for trainee assessment. 18,19 These assessments have been shown in prospective studies to have good construct validity, which is mandatory for a competency evaluator, and excellent reliability, while being superior to other assessment tools. 18,20,21 It has been suggested that WBA assessments should continue throughout training, at an approximate rate of one per week.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 These assessments have been shown in prospective studies to have good construct validity, which is mandatory for a competency evaluator, and excellent reliability, while being superior to other assessment tools. 18,20,21 It has been suggested that WBA assessments should continue throughout training, at an approximate rate of one per week. 13 A total of 76 WBAs relating to the four index procedures (61 PBAs, 15 CBDs) were undertaken during the EGS blocks, at approximately seven per month.…”
Section: Discussionmentioning
confidence: 99%